Ethnographic Analysis Of Folk Games (Texas Journal of Multidisciplinary Studies, 2025)
This article presents an ethnographic analysis of games characteristic of the economic traditions of folk games. Games among the people are permanent, seasonal, even urban-rural, for older and younger people, day and night. Depending on the number of participants in them, the games are divided into types such as children's, adolescents, youth, girls, women's and men's games. While analyzing the ethnic aspects associated with folk games, the important aspects of the issue of the existence of common games that are equally widespread among the Uzbek, Tajik and Kyrgyz nationalities living in this region are analyzed